2010
DOI: 10.1007/s11605-010-1212-0
|View full text |Cite
|
Sign up to set email alerts
|

Binding Versus Conventional Pancreaticojejunostomy After Pancreaticoduodenectomy: A Case-Matched Study

Abstract: Results of this study showed that binding pancreaticojejunostomy after pancreaticoduodenectomy was not associated with lower postoperative pancreatic fistula and moreover seems to increase postpancreatectomy hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 32 publications
(57 reference statements)
1
33
0
2
Order By: Relevance
“…Some authors have named the pancreatic anastomosis the Achilles heel of pancreatic surgery [4]. Hence, numerous surgical techniques and devices have been proposed to prevent fistula formation, such as use of the duct-to-mucosa technique, binding pancreaticojejunostomy, pancreaticogastrostomy reconstruction, Roux-en-Y reconstruction, omental wrapping around the pancreaticojejunostomy, early removal of the drain, but the best technique is still a subject of debate [5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Some authors have named the pancreatic anastomosis the Achilles heel of pancreatic surgery [4]. Hence, numerous surgical techniques and devices have been proposed to prevent fistula formation, such as use of the duct-to-mucosa technique, binding pancreaticojejunostomy, pancreaticogastrostomy reconstruction, Roux-en-Y reconstruction, omental wrapping around the pancreaticojejunostomy, early removal of the drain, but the best technique is still a subject of debate [5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…However, two French studies failed to reproduce the same results. In the study by Maggiori et al [22], a conventional PJ and binding technique had a similar fistula rate, but healing of the fistula took longer in patients with PJ carried out using Peng’s technique compared to conventional PJ (29 vs. 9 days). Incidence of hemorrhage was also higher in the binding technique (6/22 vs. 0/25).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this anastomosis were excellent in a randomized clinical trial conducted by the promoter of this technique [13] , but so far have not been confirmed in two prospective studies in 2010 [14,15] . More recently, a prospective, but not randomized, study showed that the method described by Peng is safe but is not associated with a lower frequency of PF, morbidity or mortality in comparison with the duct-to-mucosa anastomosis [16] .…”
Section: Pj By Invaginationmentioning
confidence: 92%